Takhrij and Syarah Hadith of Agrotechnology Ingredients and Benefits of Dates - Abyan Nur Fauzi; Wahyudin Darmalaksana; Mi'raj Fuadi (UIN Sunan Gunung Djati Bandung, 2021)
The purpose of this research is to discuss the hadith of the Prophet. about the Content and Benefits of Dates. This research method is qualitative through the takhrij and sharah hadith approaches with agrotechnological analysis. The results and discussion of this research is the hadith about the content and benefits of dates until the hadith of Imam Muslim History No. 1552. The conclusion of this research is takhrij and syarah hadith of the Prophet. about Ingredients and Benefits Dates are a plant that has various properties and dates are also a plant that is very blessed by Allah SWT.